Адміністративно-правове забезпечення юридичного супроводження статутної діяльності закладів вищої освіти України : дисертація - Мельник, Т. М.; Melnyk, T. M.; Невядовський, В. О. - науковий керівник (Харківський національний університет внутрішніх справ, 2024)
Дисертаційне дослідження присвячено визначенню сутності, змісту та особливостей адміністративно-правового забезпечення юридичного супроводження статутної діяльності закладів вищої освіти України, розробленню пропозицій та рекомендацій, спрямованих на вдосконалення адміністративного законодавства у відповідній сфері. Визначаються методологічні засади юридичного супроводження статутної діяльності закладів вищої освіти України. Характеризується адміністративно-правовий механізм юридичного супроводження статутної діяльності закладів вищої освіти. Визначаються напрями удосконалення юридичного супроводження статутної діяльності закладів вищої освіти України.

The thesis is devoted to the determination of the essence, content and features of administrative and legal support for the legal support of statutory activities of higher education institutions of Ukraine, to the development of proposals and recommendations aimed at improving administrative legislation in the relevant field. It has been determined that legal support of the statutory activities of a higher education institution is a complex of legal services and consultations that are provided by legal support specialists to ensure the legality and compliance with statutory requirements of all aspects of the functioning of a higher education institution. It has been noted that the content of legal support includes risk analysis, the development of strategies for solving legal issues, negotiations, the conclusion and analysis of agreements, as well as the resolution of conflict situations. It has been emphasized that the legal support of the statutory activity of the institution of higher education includes an individual approach to identifying needs and adapting strategies and solutions to the specifics of the internal organization. In the context of the peculiarities of the legal support of the statutory 20 activities of higher education institutions in Ukraine, it has been stated that the legal support of the statutory activities of higher education institutions in Ukraine is not only a process of developing normative documents but also an important mechanism for ensuring the development of higher education in the country, improving its quality and compliance with international educational standards. It is noted that institutions of higher education in Ukraine face a number of problems in the field of legal support of statutory activities, which largely determine the specifics of appropriate legal support, in particular, an unstable and changing regulatory and legal environment, an insufficient number of qualified specialists in the field of jurisprudence to meet the needs of legal support statutory activity of higher education institutions in Ukraine, limited financing of higher education institutions, insufficient automation of processes of technical support of legal provision. Such proposals regarding the improvement of administrative legislation as well as ensuring the clarity and consistency of legal norms related to the statutory activities of higher education institutions have been singled out; creation of flexible and adaptive rules that take into account rapid changes in the educational sphere and society as a whole; ensuring an effective mechanism of interaction between institutions of higher education and state bodies; ensuring proper protection of the rights and interests of participants in the educational process, in particular those seeking education, teachers and administration; the development of mechanisms for supporting education seekers and teachers in solving legal issues that arise in the process of obtaining education and scientific activity have been singled out; maintenance of professional development of employees engaged in legal support of activities of higher education institutions; integration of best practices and international management standards of higher education institutions; involvement of the public in the decision-making process in the field of higher education; maintaining the independence of higher education institutions and guaranteeing their academic freedom.

Диссертационное исследование посвящено определению сущности, содержания и особенностей административно-правового обеспечения юридического сопровождения уставной деятельности учреждений высшего образования Украины, разработке предложений и рекомендаций, направленных на усовершенствование административного законодательства в соответствующей сфере. Определяются методологические принципы юридического сопровождения уставной деятельности учреждений высшего образования Украины. Характеризуется административно-правовой механизм юридического сопровождения уставной деятельности учреждений высшего образования. Определяются направления усовершенствования юридического сопровождения уставной деятельности учреждений высшего образования Украины.
Administrative and legal support of legal support of statutory activities of higher education institutions of Ukraine
Keywords: Україна; Дисертації. Theses. Диссертации; 081 – Право; 081; 12.00.07; юридичне супроводження; статутна діяльність; заклади вищої освіти; правове регулювання; адміністративне законодавство; воєнний стан; публічне управління; публічне адміністрування; нагляд; контроль; Ukraine; legal support; statutory activity; institutions of higher education; legal regulation; administrative legislation; martial law conditions; martial law; public management; public administration; supervision; control